VAP-PLGA microspheres (VAP-PLGA) promote adipose-derived stem cells (ADSCs)-induced wound healing in chronic skin ulcers in mice via PI3K/Akt/HIF-1α pathway. Issue 2 (20th December 2021) - Jiang, Wen; Zhang, Jun; Zhang, Xudong; Fan, Chenghong; Huang, Jinlong
ABSTRACT: Chronic skin ulcers are a primary global health problem. Velvet antler polypeptide (VAP) regulates endothelial cell migration and angiogenic sprout. Adipose-derived stem cells (ADSCs) are reported to make pivotal impacts upon wound healing. This study aimed to explore the role of VAP combined with ADSCs in wound healing of chronic skin ulcers. The effect of VAP on phenotypes of ADSCs, and VAP (PLGA microspheres) combining with ADSCs on wound healing of chronic skin ulcers in vivo was evaluated. VAP generally promoted the proliferation, migration and invasion of ADSCs, and ADSC-induced angiogenesis in human umbilical vein endothelial cells (HUVECs) through PI3K/Akt/HIF-1α pathway. VAP-PLGA (PLGA microspheres) enhanced the promoting effect of ADSCs on wound healing, pathological changes, and angiogenesis in chronic skin ulcers in vivo . VAP-PLGA intensified the effect of ADSCs on up-regulating the levels of p-PI3K/PI3K, p-Akt/Akt, HIF-1α, vascular endothelial growth factor (VEGF), stromal cell-derived factor-1 (SDF-1), C-X-C motif chemokine receptor 4 (CXCR4), angiopoietin-4 (Ang-4), VEGF receptor (VEGFR), and transforming growth factor-β1 (TGF-β1), and down-regulating the levels of interleukin-1 β (IL-1β), IL-18 and IL-6 in wound tissues in chronic skin ulcers in vivo . Collectively, VAP promoted the growth, migration, invasion, and angiogenesis of ADSCs through activating PI3K/Akt/HIF-1α pathway, and VAP-PLGA enhanced the function of ADSCs in promoting wound healing in vivo, which was associated with angiogenesis, inflammation inhibition, and dermal collagen synthesis.